Immune-Mediated Repair: A Matter of Plasticity - Laurent, Paôline; Jolivel, Valérie; Manicki, Pauline; Chiu, Lynn; Contin-Bordes, Cécile; Truchetet, Marie-Elise; Pradeu, Thomas (Frontiers in Immunology, 2017)
Though the immune system is generally defined as a system of defense, it is increasingly recognized that the immune system also plays a crucial role in tissue repair and its potential dysregulations. In this review, we explore how distinct immune cell types are involved in tissue repair, and how they interact in a process that is tightly regulated both spatially and temporally. We insist on the concept of immune cell plasticity which, in recent years, has proved fundamental for the success/understanding of the repair process. Overall, the perspective presented here suggests that the immune system plays a central role in the physiological robustness of the organism, and that cell plasticity contributes to the realization of this robustness.